Analisis Risiko K3 Proyek Gedung Laboratorium Universitas Khairun Menggunakan HIRARC - Asril Hi Djen; Edward Rizky Ahadian; Sabaruddin Sabaruddin; Annisa Rimadantia Samudra (Fakultas Teknik Universitas Khairun, 2026)
Construction projects have a high level of risk, especially in occupational health and safety aspects. The laboratory building construction project at Khairun University (Unkhair) is a strategic infrastructure development that requires systematic risk management to minimize potential accidents and project losses. This study aims to identify potential hazards, assess risk levels, and determine the highest risk activities in the Unkhair laboratory building project using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. This research employed a quantitative descriptive approach. Primary data were collected through observation, interviews, and questionnaires involving 30 respondents from contractors and subcontractors. Risk assessment was conducted by analyzing likelihood and severity using a risk matrix based on HIRARC standards. The results identified 25 potential hazards categorized into 7 moderate risks, 16 high risks, and 2 extreme risks. Extreme risk levels were found mainly in electrical installation works and lightweight steel installation at height. Recommended risk controls include engineering controls, administrative controls, implementation of standard operating procedures (SOP), certified training, and mandatory use of personal protective equipment (PPE). The study concludes that HIRARC is effective in identifying and prioritizing occupational safety risks in building construction projects and can serve as a practical reference for improving safety performance in similar projects